Artificial Intelligence in Educational Assessment: Potentialities and Limitations - Rios-Munoz, D (UNIV ESTADUAL SUDOESTE BAHIA, 2025)
This article discusses the potentialities and limitations of using artificial intelligence (AI) in educational assessment. We examine how AI can provide functions such as automation of assessment processes, personalization of student learning, and real-time feedback to teachers and students. Nevertheless, we problematize ethical and practical challenges, such as limitations in understanding social, cultural, and emotional contexts, the reinforcements of biases, and the possibility of undermining the teachers work. In the face of this, we argue the need for careful use of AI to complement and enhance teaching activities and ensure human interaction as a core characteristic of educational processes